Laboratory investigation of the spatial thermodynamic properties of the bridge approach in the permafrost region - Yin, Qixiang; Wu, Junjie; Zhang, Boyang; Hou, Mingjiao (Frontiers in Earth Science, 2024)
As the highest altitude and the longest plateau railway, the Qinghai-Tibet Railway passes through a large area of continuous permafrost. As the key position of the combination of roadbed and bridge, the stability and strength of the bridge approach directly affect the smoothness of the whole line. Through indoor model test, the distribution pattern of space temperature field and the change law of temperature measuring points in the bridge approach of gravel sandwich are studied. With the increase of the depth from the subgrade surface, the influence of the temperature change of the upper atmosphere decreases gradually at the center of the subgrade 2.5m platform back, and there is an obvious lag. By comparing the temperature measurement data of different bridge approach of gravel interlayer road bridge and the bridge approach of U-shaped block gravel road bridge, it is shown that the U-shaped structure not only has a better overall cooling effect, but also the cooling effect gradually increases with the increase of the distance from the abutment back. The influence range of the road-bridge transition section on the spatial temperature field is about 14 m in the back of the abutment, and the influence is the most severe in the range of 7.5 m. The research results have important practical significance and engineering application value for the operation and maintenance of Qinghai-Tibet Railway.